Ceria‐Zirconia/Zeolite Bifunctional Catalyst for Highly Selective Conversion of Syngas into Aromatics. Issue 20 (24th August 2018) - Huang, Zhen; Wang, Sheng; Qin, Feng; Huang, Liang; Yue, Yinghong; Hua, Weiming; Qiao, Minghua; He, Heyong; Shen, Wei; Xu, Hualong
Abstract: Ceria‐zirconia solid solutions with tunable surface oxygen vacancy have been used in the direct conversion of syngas into aromatics after coupling with ZSM‐5 zeolite. A high selectivity of 83.1 % to aromatics has been achieved from syngas with low H2 /CO ratio over Ce0.2 Zr0.8 O2 /ZSM‐5 bifunctional catalyst. The surface oxygen vacancy of Ce0.2 Zr0.8 O2 is supposed to facilitate the formation of oxygenates which act as intermediates for C−C coupling and aromatization on ZSM‐5, and thus contribute to the well kinetic matching between C−O activation and C−C coupling over these two components of catalyst. The ceria‐zirconia with abundant surface oxygen vacancies and enhanced lattice oxygen mobility intimately mixed with ZSM‐5 zeolite with moderate acidity and crystal size play an important role in the catalytic performance. Abstract : O‐pen vacancy : By tuning the surface oxygen vacancy of ceria‐zirconia solid solutions, a well kinetic matching between C−O activation and C−C coupling can be achieved, and syngas with low H2 /CO ratio is directly converted into aromatics with a high selectivity over a ceria‐zirconia/HZSM‐5 bifunctional catalyst.